(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The emergence of e-marketing to make the world a small village does not comply with barriers, the place nor the time, which led to the transformation of marketing in various service sectors, regional and international general and the insurance sector, especially from traditional marketing to electronic marketing, bringing e-marketing of insurance services is the effective tool to achieve for growth, was able to jump to the overall marketing efforts to the contemporary trends in line with the current and its variables, and this significant acceleration in technological development has made insurance companies are racing to offer their insurance services on the latest applications of modern technology through multiple sites on the Internet .